1.
"A=\\begin{pmatrix}\n 2 & -2 \\\\\n 3 & 3\n\\end{pmatrix}, x=\\begin{pmatrix}\n 4 \\\\\n 1 \n\\end{pmatrix}"
"Ax=\\begin{pmatrix}\n 2 & -2 \\\\\n 3 & 3\n\\end{pmatrix}\\begin{pmatrix}\n 4 \\\\\n 1 \n\\end{pmatrix}=\\begin{pmatrix}\n 2\\cdot4+(-2)\\cdot1 \\\\\n 3\\cdot4+3\\cdot1 \n\\end{pmatrix}="
"=4\\begin{pmatrix}\n 2 \\\\\n 3\n\\end{pmatrix}+1\\begin{pmatrix}\n -2 \\\\\n 3 \n\\end{pmatrix}" 2.
The solution set of the homogeneous system Ax = 0 is given by the formulas
"x_1=-5r+6s, x_2=r-3s,x_3=r,x_4=s" The solution can be written in matrix form. Then
"\\begin{bmatrix}\n x_1 \\\\\n x_2 \\\\\n x_3 \\\\\n x_4 \n\\end{bmatrix}=\\begin{bmatrix}\n -5r+6s \\\\\n r-3s \\\\\n r \\\\\n s \n\\end{bmatrix}=r\\begin{bmatrix}\n -5 \\\\\n 1 \\\\\n 1 \\\\\n 0 \n\\end{bmatrix}+s\\begin{bmatrix}\n 6 \\\\\n -3 \\\\\n 0 \\\\\n 1 \n\\end{bmatrix}" Then
"x=r\\begin{bmatrix}\n -5 \\\\\n 1 \\\\\n 1 \\\\\n 0 \n\\end{bmatrix}+s\\begin{bmatrix}\n 6 \\\\\n -3 \\\\\n 0 \\\\\n 1 \n\\end{bmatrix}"
3.
The solution set of the homogeneous system Ax = 0 is given by the formulas
"x_1=-5r+6s, x_2=r-4s,x_3=r,x_4=s" The solution can be written in matrix form. Then
"\\begin{bmatrix}\n x_1 \\\\\n x_2 \\\\\n x_3 \\\\\n x_4 \n\\end{bmatrix}=\\begin{bmatrix}\n -5r+6s \\\\\n r-4s \\\\\n r \\\\\n s \n\\end{bmatrix}=r\\begin{bmatrix}\n -5 \\\\\n 1 \\\\\n 1 \\\\\n 0 \n\\end{bmatrix}+s\\begin{bmatrix}\n 6 \\\\\n -4 \\\\\n 0 \\\\\n 1 \n\\end{bmatrix}"
The solution set of the non homogeneous system Ax = b is given by the formulas
"x_1=-3, x_2=4,x_3=1,x_4=-2" The solution can be written in matrix form. Then
"\\begin{bmatrix}\n x_1 \\\\\n x_2 \\\\\n x_3 \\\\\n x_4 \n\\end{bmatrix}=\\begin{bmatrix}\n -3 \\\\\n 4 \\\\\n 1 \\\\\n -2\n\\end{bmatrix}"
Hence the general solution is
"x=\\begin{bmatrix}\n -3 \\\\\n 4 \\\\\n 1 \\\\\n -2\n\\end{bmatrix}+r\\begin{bmatrix}\n -5 \\\\\n 1 \\\\\n 1 \\\\\n 0 \n\\end{bmatrix}+s\\begin{bmatrix}\n 6 \\\\\n -4 \\\\\n 0 \\\\\n 1 \n\\end{bmatrix}"
Comments
Leave a comment